Influenza vaccination-induced H3 stalk-reactive memory B-cell clone expansion. Issue 5 (27th January 2023) - Long, Zhaoyi; He, Jiang; Shuai, Qinglu; Zhang, Ke; Xiang, Jim; Wang, Huan; Xie, Shuang; Wang, Shengyu; Du, Wensheng; Yao, Xinsheng; Huang, Junqiong
Abstract: Current vaccine formulations elicit a recall immune response against viruses by targeting epitopes on the globular head of hemagglutinin (HA), and stalk-reactive antibodies are rarely found. However, stalk-specific memory B-cell expansion after influenza vaccination is poorly understood. In this study, B cells were isolated from individuals immunized with seasonal tetravalent influenza vaccines at days 0 and 28 for H7N9 stimulation in vitro . Plasma and supernatants were collected for the analysis of anti-HA IgG using ELISA and a Luminex assay. Memory B cells were positively enriched, and total RNA was extracted for B cell receptor (BCR) H-CDR3 sequencing. All subjects displayed increased anti-H3 antibody secretion after vaccination, whereas no increase in cH5/3-reactive IgG levels was detected. The number of shared memory B-cell clones among individuals dropped dramatically from 593 to 37. Four out of 5 subjects displayed enhanced frequencies of the VH3-23 and VH3-30 genes, and one exhibited an increase in the frequency of VH1-18, which are associated with the stalk of HA. An increase in H3 stalk-specific antibodies produced by B cells stimulated with H7N9 viruses was detected after vaccination. These results demonstrated that H3 stalk-specific memory B cells can expand and secrete antibodies that bind to the stalk in vitro, although no increase in serum H3 stalk-reactive antibodies was found after vaccination, indicating potential for developing a universal vaccine strategy.